2014
DOI: 10.1007/s00018-014-1613-4
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation for amyotrophic lateral sclerosis: therapeutic potential and perspectives on clinical translation

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurological disease characterized by degeneration of upper and lower motor neurons. There are currently no clinically impactful treatments for this disorder. Death occurs 3-5 years after diagnosis, usually due to respiratory failure. ALS pathogenesis seems to involve several pathological mechanisms (i.e., oxidative stress, inflammation, and loss of the glial neurotrophic support, glutamate toxicity) with different contributions from environmental and genetic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 54 publications
0
43
0
2
Order By: Relevance
“…Currently available ALS models do not entirely recapitulate the human pathology, thus raising the question whether screening therapeutic compounds in such models may prove beneficial in humans. In this regard, the advent of iPSC-based models may represent a valuable approach for future research (Faravelli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Currently available ALS models do not entirely recapitulate the human pathology, thus raising the question whether screening therapeutic compounds in such models may prove beneficial in humans. In this regard, the advent of iPSC-based models may represent a valuable approach for future research (Faravelli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MSCs from one patient with a favorable response to autologous MSCs were tested in SOD1 mice and found to prolong survival more than MSCs from patients who had failed to improve, illustrating the potential of animal models to help evaluate clinical observations as trials progress . The reader is referred to other more comprehensive reviews for additional details regarding ongoing cell therapy trials for ALS (Antonic et al, 2013;Donnelly et al, 2012;Faravelli et al, 2014;Thomsen et al, 2014) …”
Section: Alsmentioning
confidence: 99%
“…There have been ongoing human trials with MSC on ALS treatment with completed human trial data (human clinical trials data as time of review paper written, https://clinicaltrials.gov) [7, 8, 17]. In 2010, Mazzini et al reported phase 1 trial data with MSC transplant in ALS patients in Italy [18].…”
Section: Cell-based Therapy For Alsmentioning
confidence: 99%
“…The neurotropic effects were effective enough to revive the ALS animals, which consisted mostly of SOD1 rodents. Current ongoing human trials will give better understanding of cord blood cells against ALS [17, http://clinicaltrials.org]. …”
Section: Cell-based Therapy For Alsmentioning
confidence: 99%
See 1 more Smart Citation